THE ROLE OF GLOBALIZATION IN THE ESTABLISHMENT OF PUBLIC ADMINISTRATION AS A COMPONENT OF THE NEW INTERNATIONAL ORDER - Yuliia Horenko (Публічне управління та регіональний розвиток)
The article examines the role and significance of globalization for the formation, development and transformation of public administration in the State with a view to determining its place in the new international order.